Morphological evaluation of the quadriceps tendon using preoperative ultrasound in anterior cruciate ligament injured knee (114). Issue 10 (31st October 2021) - Takeuchi, Satoshi; Kanto, Ryo; Rothrauff, Benjamin; Byrne, Kevin; Fu, Freddie; Onishi, Kentaro
Objectives: The quadriceps tendon (QT) is one of the potential autografts used for anterior cruciate ligament (ACL) reconstruction, and excellent clinical results have been reported using QT autograft with or without a patellar bone block. In the coronal plane, QT autografts are commonly harvested from the central 10 mm of the tendon. To adequately reconstruct the native length of the ACL with an additional 15-20 mm to fill each bone tunnel, 65-70 mm of QT length is typically required to use an all soft tissue graft. However, a previous study has reported the length of the QT to vary from 53.9-104.0 mm between individuals when assessed with 3D-MRI. Additionally, the minimum width of the QT 70 mm proximal to the superior pole of the patella was found to be just 9.6 mm. Due to such variability in morphology, the QT should be evaluated prior to surgery to avoid harvesting an inadequately sized graft. However, to the best of our knowledge, QT morphology has not been evaluated pre-operatively in ACL injured knees. Furthermore, 3D-MRI is not typically used in daily practice for ACL injury, and it is difficult to evaluate the entire QT using the standard MRI protocol for ACL injury. Ultrasound is a readily available imaging modality and has several advantages compared to MRI, such as decreased examination cost and time. Thus, we aimed to investigate the morphological characteristics of the QT using preoperative ultrasound in ACL injured knees. Methods: A total of 33 patients (17 males and 16 females, 17 right and 16 left knees), who were diagnosed with an ACL tear requiring ACL reconstruction were prospectively included. Preoperative ultrasonographic examination was performed by a fellowship-trained musculoskeletal ultrasound specialist using a 18-5 MHz linear ultrasound transducer (Aplio i800, Canon medical systems, Japan). Patients were positioned supine with 20˚ of knee flexion. The transducer was placed on the anterior aspect of the knee perpendicular to the longitudinal axis of the QT to visualize the QT in the short axis. Short axis images were acquired at 30, 50, 60, 70, 80, 90 and 100 mm proximal to the superior pole of the patella. The length of the QT was determined by the two contiguous images that did and did not contain rectus femoris muscle tissue (i.e., if the rectus femoris muscle could be seen from 90 mm proximal to the superior pole of the patella, the length was 80-90 mm). All images with rectus femoris muscle belly were excluded from further width, thickness and CSA assessment. For each image, the width of the superficial and narrowest part of the QT, and the thickness of the central and thickest part of the QT were assessed (Figure 1). In addition, the cross-sectional area (CSA) was assessed at the central 10 mm of the width of the QT to simulate intraoperative harvesting of the QT (Figure 2). Estimated intraoperative diameter of the QT autograft was calculated based on the formula [(intraoperative diameter of the QT autograft) = 6.818 + 0.045 × (QT CSA)] created through the linear regression analysis between the CSA of the QT and intraoperative diameter of the QT autograft in a previous study. All data of the width, thickness, and CSA of the QT were compared among all assessment locations using one-way ANOVA followed by post hoc pairwise comparison using a Tukey test. The QT length was classified into 7 groups of 0-30, 30-50, 50-60, 60-70, 70-80, 80-90, 90-100 and 100 < mm, and demographic data (age, sex, height, weight and BMI) was compared among these groups using a one-way ANOVA or a Fisher exact test to reveal the relationship between the QT length and demographic data. Statistical significance was set at P<0.05. Results: Mean age, height, weight, and body mass index were 26.0 ± 11.5 years, 173.8 ± 11.5 cm, 72.6 ± 14.5 kg, and 23.9 ± 3.2 kg/m 2, respectively. The QT length was 50-60 mm in 4 patients, 60-70 mm in 11 patients, 70-80 mm in 10 patients, 80-90 mm in 6 patients, 90-100 mm in 1 patient, and longer than 100 mm in 1 patient. No significant relationship was observed between the QT length and all demographic data (P>0.05). The mean QT thickness, width, and CSA at each position were shown in Table 1. All of the width, thickness, and CSA of the QT were significantly greater at 30 mm than 70 mm proximal to the superior pole of the patella. The estimated intraoperative diameter of the QT autograft was 0.6-0.7 mm greater at 30 mm than that at 70 and 80 mm. Regarding the range of the width of the QT, the minimum width of the narrowest segment of the QT was less than 10 mm wide at 60, 70, 80, and 90 mm in 5 patients. The minimum width of the superficial part of the QT was less than 10 mm wide at 60 and 70 mm in 2 patients. Conclusions: The important finding of this study was that the length of the QT was less than 70 mm in 45.5% of patients (15/33). Moreover, minimum width of the narrowest QT was shorter than 10 mm in 5 patients. These results indicate that approximately half of the patients may have had inappropriate QT width or length to be harvested as an all soft tissue QT autograft. In addition, all of the QT width, thickness, CSA, and estimated intraoperative diameter of the QT autograft were significantly greater at 30 mm than 70 mm proximal to the superior pole of the patella. Since the intraoperative diameter of the graft is commonly measured using a graft sizing device with 0.5 mm increments, the difference of the estimated diameter can be considered as clinically meaningful difference. Therefore, the size of the proximal part of the QT autograft can be smaller than distal part if the QT autograft is harvested to 70 mm or more proximal to the superior pole of the patella. Thus, preoperative assessment of the morphological characteristics of the QT using ultrasound may help to avoid inadequately sized grafts and may determine if a patellar bone block is needed to extend the length of the QT autograft.